Integrative Teaching Material with Project-based Learning Approach to Improve Elementary School Students’ Bilingual Literacy and Numeracy Skills - Sumarno, Wahyu Kyestiati; Shodikin, Ali; Solikha, Nur Imro’atus; Pratama, Novandi Kevin; Valensiana, Brigita Febi (International Journal of Elementary Education, 2022)
The availability of teaching materials with a project-based approach to improving bilingual literacy skills still needs to be improved. An alternative solution is to develop project-based integrative teaching materials. This study examines the feasibility of project-based integrative teaching materials in the form of books, and an application called the TOY App. This research is research and development following the Thiagarajan model. This study involved 3 learning experts who validated books and applications in three aspects: material, language, and design, and 10 students. Data collection through product validation sheets and questionnaires. Data were analyzed by calculating the average percentage of each aspect. The results of the expert validation show that both the book and the application have a very good level of validity, with an average percentage of 87.1% for the material aspect, 85.6% for the language aspect, and 88.3% for the design aspect. The TOY App obtains 82.7% for material aspects, 83.1% for language aspects, and 85.7% for design aspects. The student's response to the book is in the good criteria, and the application category is very good. This study showed that integrative teaching materials, in the form of project-based literacy and numeracy books and the learning application "TOY App," received very good responses from expert validators and students. These results indicate that the project-based integrative book and the TOY App application are feasible.